2021
DOI: 10.1128/spectrum.00642-21
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Mobbing-Like Behavior against Acanthamoeba castellanii Bacterivore and Its Rapid Control by Quorum Sensing and Environmental Cues

Abstract: Pseudomonas aeruginosa was shown previously to attack amoebae and other predators by adhering to them and injecting them with virulent substances. In this work, we show that an active, coordinated group behavior is enacted by the bacteria to utilize these molecular components, responding to both predator and bacterial population density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…When comparing different mutants ( Fig. 4 ), results fit our current understanding of P. aeruginosa adhesion behavior– bacteria readily adhere to eukaryotic cells [ 22 , 23 ], using the flagellum for initial adhesion to the surface of the cells [ 24 ]. This causes flagella mutants (Δ flg F and Δ fli C) to display no significant adhesion kinetics ( Fig.…”
Section: Resultsmentioning
confidence: 55%
“…When comparing different mutants ( Fig. 4 ), results fit our current understanding of P. aeruginosa adhesion behavior– bacteria readily adhere to eukaryotic cells [ 22 , 23 ], using the flagellum for initial adhesion to the surface of the cells [ 24 ]. This causes flagella mutants (Δ flg F and Δ fli C) to display no significant adhesion kinetics ( Fig.…”
Section: Resultsmentioning
confidence: 55%
“…2A and B ). According to a previous study, we suggested that the fluorescence results were caused by bacterial attachment, not amoeba phagocytosis ( 24 ). In addition to adhering to amoebae, P. aeruginosa invasion starts with sensing and adhering to host cells ( 25 , 26 ).…”
Section: Resultsmentioning
confidence: 93%
“…Previous research suggests that P. aeruginosa can sense amoebae and attack them by adhering to the amoeba surface ( 19 , 24 ). The images in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the expression of the toxin-based bacterial defense is assumed to be jointly controlled by predator recognition and quorum sensing (QS). Examples for such joint control of bacterial defenses have been reported previously [8,26,51]. The involvement of QS in chemical defense strategies is particularly likely as effective toxin concentrations can only be reached when producers are highly abundant.…”
Section: Predator Recognition and Quorum Sensing Interactmentioning
confidence: 97%